Bugs and spiders - Taylor, Barbara, 1954- (Columbus, Ohio : Waterbird Books, 2003)
Close-up photographs and simple text introduce such creatures as a rhino beetle, cockroach, praying mantis, cicada, millipede, and tarantula.
First published by Ticktock Media Ltd.: Great Britain, c2002.
Includes index.
Library Media Connection.
4.2
K-3
Keywords: Insects -- Juvenile literature; Spiders -- Juvenile literature; Insects; Insects